Heat insulating sheet and manufacturing method thereof, as well as electronic device and battery unit
A composite heat insulating sheet with high-density aerogel and non-woven fibers, produced using a controlled drying process, addresses the collapse issue under high loads, maintaining effective thermal resistance and compression resistance for battery modules and electronic devices.
Patent Information
- Application Number
- JP2023107024
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2039-05-29
AI Technical Summary
Conventional insulation sheets made of silica aerogel collapse under high loads, leading to a significant reduction in insulation effectiveness, and existing methods cannot produce high-density aerogels with sufficient strength and thermal resistance for use in battery modules and electronic devices.
A composite production method involving non-woven fibers impregnated with a sol prepared by adding carbonate ester to a water glass composition, followed by a controlled drying process, results in a heat insulating sheet with high-density aerogel and non-woven fibers, maintaining low compressibility and high thermal resistance.
The heat insulating sheet achieves a compression ratio of 40% or less at 5MPa and a thermal resistance of 0.01 m² K/W or more, effectively preventing thermal chain reactions and ensuring insulation even under high loads.
Smart Images

Figure 0007603213000002 
Figure 0007603213000003 
Figure 0007603213000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a heat insulating sheet, a manufacturing method thereof, and an electronic device and an electronic unit using the heat insulating sheet. In particular, the present disclosure relates to a high-strength heat insulating sheet, a manufacturing method thereof, and an electronic device and a battery unit. [Background technology]
[0002] In the fields of automotive and industrial equipment, there is a demand for high-performance heat insulating sheets with excellent compression properties to control the heat flow from heat-generating components in small spaces, and to ensure product safety and fire prevention. For example, such heat insulating sheets are expected to be used as separators between cells in lithium-ion battery modules.
[0003] The safety standard for lithium-ion batteries requires that anti-flamming tests be performed. Anti-flamming tests are a method for testing whether or not a thermal chain reaction that leads to fire or explosion in other cells, including adjacent cells, occurs when one cell in a battery module goes into thermal runaway. To prevent thermal runaway in adjacent cells, there is a safety design concept of sandwiching a material with excellent thermal insulation between the cells. In theory, even with materials with high thermal conductivity, it is possible to prevent thermal chain reaction and fire to some extent by making the material thicker.
[0004] However, because battery modules are installed inside devices, the space in which they can be installed is limited, and there are size restrictions, making it difficult to simultaneously increase the capacity of the modules while making them fire-resistant and compact.
[0005] To achieve both of these goals, a thin, highly insulating material is desired for the cell separator. In addition, considering that the active material will degrade and expand during the charge / discharge cycle of the battery, causing the cell to swell, it is also desirable for the insulating sheet to have properties that make it difficult to crush. During the initial assembly of the battery module, the load on the insulating sheet, which acts as the cell separator, is relatively small, at 1 MPa or less.
[0006] On the other hand, when the battery expands, the heat insulating sheet may be subjected to a load of up to 5 MPa, so it is important to design the heat insulating sheet material taking into account its compression characteristics.
[0007] Silica aerogel is known as a material with low thermal conductivity. Silica aerogel consists of a network structure in which silica particles of the order of several tens of nanometers are connected by point contact, and its average pore size is 68 nm or less, which is the mean free path of air. In other words, it has a lower thermal conductivity than still air. Therefore, silica aerogel has attracted attention as an excellent heat insulating material. However, one of the practical issues is that it has extremely low strength against various deformation modes such as compression, bending, and shear.
[0008] The inventors have devised a thin, homogeneous sheet-like insulation material that is easier to handle by combining silica aerogel with nonwoven fibers (Patent Document 1). This thin insulation sheet is easy to handle and relatively strong against bending.
[0009] On the other hand, a self-supporting hard composite material has been devised as a high-strength insulating material using aerogel, in which a slurry containing hydrophobic aerogel particles, an inorganic binder such as cement, gypsum, or lime, a surfactant, and fibers is molded and dried in a container (Patent Document 2). [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Patent No. 6064149 [Patent Document 2] Patent No. 5934400 Summary of the Invention [Problem to be solved by the invention]
[0011] However, when conventional insulation sheets are used by sandwiching them between battery cells or the like, the aerogel can be compressed and crushed, especially under heavy loads, resulting in a significant reduction in the insulation effect compared to when the load is light.
[0012] Therefore, an object of the present disclosure is to provide a heat insulating sheet that can be used even under high loads, a method for manufacturing the same, and an electronic device and a battery unit using the same. [Means for solving the problem]
[0013] In order to solve the above problems, a method for producing a heat insulating sheet is used, which includes a composite production step in which a basic sol prepared by adding a carbonate ester to a water glass composition is impregnated into nonwoven fibers to produce a hydrogel-nonwoven fiber composite, and a drying step in which the liquid contained in the composite is removed by drying at a temperature lower than the critical temperature and the critical pressure of the liquid.
[0014] In addition, a heat insulating sheet containing aerogel and nonwoven fibers and having a compressive strain of 40% or less at 0.30 to 5.0 MPa is used.
[0015] Furthermore, an electronic device is used in which the heat insulating sheet is disposed between a heat generating electronic component and a housing, and a battery unit is used in which the heat insulating sheet is disposed between batteries. Effect of the Invention
[0016] The heat insulating sheet of the present disclosure is difficult to crush, with a compression rate of 40% or less at 5 MPa, and has a thermal resistance of 0.01 m 2 K / W or more. Therefore, it exhibits an effective heat transfer retardation effect even in a high-temperature compression environment. [Brief description of the drawings]
[0017] [Figure 1] A chemical formula diagram explaining the gelation mechanism of water glass by carbonate ester according to an embodiment. [Diagram 2]Flow diagram of a method for manufacturing a heat insulating sheet according to an embodiment [Diagram 3] FIG. 1 is a diagram showing the relationship between the SiO2 concentration in a water glass composition according to an embodiment and the compressibility of a heat insulating sheet. [Figure 4] FIG. 1 is a diagram showing the relationship between the SiO2 concentration in a water glass composition according to an embodiment and the thermal resistance of a heat insulating sheet. [Diagram 5] FIG. 1 is a diagram showing the relationship between the SiO2 concentration in a water glass composition according to an embodiment and the thermal conductivity of a heat insulating sheet. [Figure 6] FIG. 1 is a diagram showing the relationship between the SiO2 concentration in the water glass composition of the embodiment and the bulk density of the heat insulating sheet. [Figure 7] 1 is a cross-sectional view of an electronic device as an application example of the heat insulating sheet according to the embodiment. [Figure 8] FIG. 1 is a cross-sectional view of a battery unit as an application example of the heat insulating sheet according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Next, the present disclosure will be described with reference to preferred embodiments.
[0019] <Thermal insulation sheet design concept> Several aerogel composite insulation sheets made of silica aerogel and nonwoven fibers have been known so far. Many of them are improving in terms of handling. However, they are still lacking in strength to withstand a compression of 5 MPa and a 0.01 m2 diameter when compressed. 2 It did not have a high thermal resistance of 100K / W or more.
[0020] In contrast, the heat insulating sheet of the present embodiment is made of at least two components, high-density aerogel and nonwoven fiber, and has high strength. This is due to the "high-density aerogel" densely and without gaps compounded in the voids of the continuous nonwoven fiber body.
[0021] Generally, silica aerogel refers to a low-density porous silica body, with a bulk density of approximately 0.3 g / cm. 3The synthesis of aerogel is usually carried out using low-concentration silica raw materials such as alkoxysilanes and water glass, and gelling agents such as mineral acids, bases, and organic acids. Conventionally, when water glass is used as a silica raw material, the silica concentration during aerogel synthesis was restricted to 6% by weight or less. This is because when a mineral acid, base, organic acid, or other gelling agent is added, the hydrolysis and dehydration condensation of sodium silicate proceeds rapidly. In other words, when the silica concentration is 7% by weight or more, the reaction rate is too fast, inducing heterogeneous nucleation and making it impossible to obtain a uniform gel.
[0022] Therefore, in the existing synthesis method of silica aerogel, it is not possible to increase the silica concentration, obtain a high density aerogel, and furthermore, it is not possible to increase the strength of the aerogel by increasing the density of the aerogel. In contrast, in the present embodiment, since the aerogel is produced by the method described below, it is possible to increase the density of the aerogel, and it is possible to obtain a heat insulating sheet containing a high density aerogel and nonwoven fabric fibers. And, according to this production method, a heat insulating sheet having the following physical properties can be obtained.
[0023] <Compressibility of heat insulation sheet> The heat insulating sheet of the present embodiment has a compression ratio of 40% or less, and more preferably 30% or less, when pressurized at 5 MPa. The compression ratio is a value measured by a bench-top precision universal testing machine (e.g., Autograph AGS-X (manufactured by SHIMADZU)).
[0024] <Thermal resistance of heat insulation sheet> The thermal resistance of the heat insulating sheet of this embodiment when pressurized at 5 MPa is 0.010 m 2 K / W or more is preferable, and 0.015m 2 It is more preferable that the thermal resistance is equal to or higher than K / W. The thermal resistance is a value calculated by dividing the thickness of the heat insulating sheet when pressed at 0.30 MPa to 5 MPa by the thermal conductivity given below.
[0025] <Thermal conductivity of heat insulation sheet> The thermal conductivity of the heat insulating sheet of the present embodiment cannot be generally determined depending on the degree of compression ratio, but it is sufficient if it is 100 mW / mK or less. The thermal conductivity is a value measured by a heat flow meter.
[0026] <Bulk density of heat insulation sheet> The bulk density of the heat insulating sheet of this embodiment is 0.3 g / cm 3 ~0.6g / cm 3 It is preferable that:
[0027] <Pore characteristics of high-density aerogel> The specific surface area of the high-density aerogel constituting the heat insulating sheet of this embodiment is 300 m 2 / g~600m 2 / g. Furthermore, the pore volume is preferably less than 1.5 ml / g. Furthermore, the average pore diameter of the high density aerogel is preferably 10 to 70 nm. The pore characteristics of the high density aerogel are values measured by a high-precision gas / vapor adsorption measurement device.
[0028] <Thickness of the insulation sheet> The thickness of the heat insulating sheet of this embodiment is preferably in the range of 0.03 mm to 3.0 mm, and more preferably in the range of 0.05 mm to 1.5 mm. If the thickness of the heat insulating sheet is thinner than 0.03 mm, the heat insulating effect in the thickness direction may decrease. If the heat insulating sheet does not realize a very low thermal conductivity at a level close to vacuum, the heat transfer in the thickness direction from one side to the other side cannot be reduced. In particular, if the thickness of the heat insulating sheet is 0.05 mm or more, the heat insulating effect in the thickness direction can be ensured. On the other hand, if the heat insulating sheet is thicker than 1.5 mm, it may be difficult to incorporate it into in-vehicle or industrial equipment. In particular, in the in-vehicle field, if the thickness is thicker than 3.0 mm, it becomes even more difficult to incorporate it into equipment.
[0029] <Content (filling rate) of high-density aerogel in heat insulation sheet> The proportion of high density aerogel in the weight of the heat insulating sheet of this embodiment cannot be generalized because the optimal range varies depending on the basis weight, bulk density, and thickness of the nonwoven fiber. However, the proportion of high density aerogel in the weight of the heat insulating sheet should be at least 50% by weight. If the proportion is less than 50% by weight, the heat resistance will be low and the strength of the heat insulating sheet will not be able to be maintained. Also, the proportion should be 80% by weight or less. If the proportion is more than 80% by weight, the heat resistance will increase, but the flexibility will be insufficient and the high density aerogel may fall off due to repeated use.
[0030] <Raw materials for heat insulation sheets> The nonwoven fibers for obtaining the heat insulating sheet of the present embodiment and the raw material types of the high-density aerogel will be described below.
[0031] (About nonwoven fabrics) <Nonwoven fiber weight> The basis weight of the nonwoven fabric used in the manufacture of the heat insulating sheet of the present embodiment is 5 to 200 g / m in order to maintain the minimum rigidity required as a support for the high-density aerogel. 2 The basis weight is the weight of the fibers per unit area.
[0032] <Bulk density of nonwoven fibers> The bulk density of the nonwoven fabric fiber is 100 to 500 kg / m from the viewpoint of increasing the content of high-density aerogel in the heat insulating sheet of the embodiment and further reducing the thermal conductivity. 3 In order to form a nonwoven fabric having mechanical strength as a continuous body, the bulk density is preferably at least 100 kg / m 3 It is also preferable that the bulk density of the nonwoven fabric fiber is 500 kg / m 3 If it is larger, the void volume in the nonwoven fabric fibers is reduced, so that the amount of high-density aerogel that can be filled is relatively reduced, and the thermal resistance value tends to be small.
[0033] <Nonwoven fiber material> The material of the nonwoven fiber used in manufacturing the heat insulating sheet of the embodiment can be inorganic fiber-based glass wool, glass paper, rock wool, resin-based polyethylene terephthalate (PET), polyphenylene sulfide (PPS), polypropylene (PP), polytetrafluoroethylene (PTFE), natural wool, cellulose, etc. Among these, inorganic fiber is particularly preferable.
[0034] (Raw materials and gelling agents for synthesizing high-density aerogel) <Raw materials for high density aerogel> The raw material for the high density aerogel is a general-purpose silica raw material such as alkoxysilane, water glass, etc. In this embodiment, a dispersion or solution in which the silica raw material is dispersed or dissolved in water by adding water to the silica raw material so that the silica concentration falls within a desired range is used.
[0035] It is believed that Na ions have an effect on the densification and density of the porous structure in high-density aerogel. Therefore, among the above-mentioned materials, water glass containing Na ions is preferably used as the silica raw material. In other words, a water glass composition in which water glass is dispersed or dissolved in water is preferably used. The silica concentration in the raw material dispersion or solution (particularly the water glass composition) is preferably high in order to synthesize a high-density aerogel, and is particularly preferably 14 to 22% by weight.
[0036] <Gelling agents and their reaction mechanisms> In this embodiment, a carbonate ester is used as a gelling agent for gelling the above-mentioned raw material species. Carbonate esters are generally not easily changed in an acidic environment, but are known to be hydrolyzed into carbonic acid and alcohol under basic conditions. In this embodiment, the carbonic acid produced by this hydrolysis is used for gelation.
[0037] The inventors have been searching for gelling agents to synthesize a new aerogel by uniformly gelling a high-concentration silica composition (particularly a water glass composition) having a silica concentration of 8% by weight or more. As a result, they have found that carbonate esters are suitable for uniformly gelling a high-concentration water glass raw material and synthesizing a high-density aerogel.
[0038] The gelling mechanism of water glass by carbonate esters is explained using the chemical reaction formula in Figure 1, taking ethylene carbonate as an example.
[0039] In the first step, ethylene carbonate 103, a type of carbonate ester, is added and dissolved in an aqueous solution (water glass composition) of sodium silicate 101, which is basic at pH 10 or higher. As a result, hydroxyl ions 102 in the raw material (water glass composition) nucleophilically attack the carbonyl carbon of ethylene carbonate 103, and hydrolysis of ethylene carbonate 103 proceeds. As a result, carbonate ions (CO3 2- ) 104 and ethylene glycol 105 are produced in the system.
[0040] In the second step, sodium silicate 101 reacts with carbonate ions 104, and a dehydration condensation reaction of silicic acid proceeds. At this time, sodium carbonate 107 is produced as a by-product. When a network structure consisting of siloxane bonds develops, the fluidity of the water glass composition disappears and the composition gels. In this way, a hydrogel 106 is obtained. Most of the sodium carbonate 107 remains in the hydrogel 106.
[0041] As described above, when a carbonate ester is used as a gelling agent, the reaction proceeds in two stages, making it possible to control the reaction rates of the hydrolysis and dehydration condensation reaction of sodium silicate 101, and achieving uniform gelation.
[0042] Specific examples of carbonate esters include dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, etc. Any carbonate ester can uniformly gel the high-concentration silica raw material (water glass composition), but as the alkyl chain of the carbonate ester becomes longer, it becomes more hydrophobic and less soluble in water. Therefore, from the viewpoint of the solubility of the carbonate ester in water and the hydrolysis reaction rate, dimethyl carbonate and ethylene carbonate, which are relatively easily soluble in water, are preferably used.
[0043] Furthermore, when the amount of carbonate ester added is 1.0 to 10.0 parts by weight per 100 parts by weight of the total amount of the silica raw material (water glass composition), a uniform gel can be prepared.
[0044] The carbonate ester may be mixed with the water glass composition in a state of being dissolved or dispersed in water. The more preferable amount of the carbonate ester to be added is 3.0 to 6.0 parts by weight per 100 parts by weight of the total amount of the water glass composition, in terms of productivity (such as the impregnation speed of the basic sol into the nonwoven fabric described below) and gelling agent cost, although the gelling time varies depending on the silica concentration and gelling agent concentration in the water glass composition. The carbonate ester is not a solvent but a gelling agent.
[0045] <Method of manufacturing heat insulating sheet> An outline of the method for producing the heat insulating sheet of this embodiment is shown in Figure 2. The basic synthesis procedure consists of three steps (a) to (c). However, step (b) is not necessarily required.
[0046] (a) Complex generation process: A basic sol prepared by mixing a water glass composition with a carbonate ester is impregnated into nonwoven fibers and gelled. The nonwoven fibers impregnated with the basic sol are sandwiched between films and the thickness is controlled using a biaxial roll or the like to produce a hydrogel-nonwoven fiber composite. At this time, the hydrogel-nonwoven fiber composite may or may not be washed with water as necessary.
[0047] (b) Substitution step: There are five patterns.
[0048] <1> The hydrogel-nonwoven fiber composite produced in step (a) is immersed in hydrochloric acid. After a certain period of time, the composite is immersed in a silylating agent and placed in a thermostatic chamber and left for a certain period of time. The hydrochloric acid is discharged from the composite, and the two liquids are separated (siloxane in the upper layer, hydrochloric acid water in the lower layer). The composite is removed and subjected to the next drying step. The water in the composite is removed using a silylating agent.
[0049] <2> The hydrogel-nonwoven fiber composite produced in step (a) is dried as is, meaning that no replacement step is carried out in this case.
[0050] <3> The water inside the hydrogel-nonwoven fiber composite produced in step (a) is replaced with an amphiphilic solvent with low surface tension, such as alcohol or acetone, and then dried.
[0051] <4> The hydrogel-nonwoven fiber composite produced in step (a) is immersed once in an aqueous hydrochloric acid solution, washed with water, and then dried.
[0052] <5> The hydrogel-nonwoven fiber composite produced in step (a) is immersed once in an aqueous hydrochloric acid solution, and then the water inside the composite is replaced with an amphiphilic solvent with low surface tension, such as alcohol or acetone, and then the composite is dried.
[0053] Any of the five patterns is acceptable. However, there are the following cases:
[0054] In patterns 2 and 3, the hydrogel is alkaline, so self-dissolution and elution occur during heating and drying, which can cause the secondary particle junctions (necks) of the silica to thicken, resulting in increased thermal conductivity.
[0055] In patterns 4 and 5, the liquid nature of the hydrogel is acidic to neutral, so that self-dissolution during heating and drying can be suppressed and an increase in thermal conductivity can be suppressed. Therefore, patterns 4 and 5 are more preferable than patterns 2 and 3.
[0056] Pattern 1 involves many steps and requires time.
[0057] (c) Drying process: The liquid contained in the hydrogel-nonwoven fiber composite obtained in step (b) is removed by drying at a temperature lower than the critical temperature and the critical pressure of the liquid. In step (a), when a carbonate ester is added as a gelling agent to the water glass composition, sodium carbonate is generated along with the dehydration condensation of silicic acid, and the sodium carbonate is sometimes taken into the gel to obtain a very basic hydrogel. In step (b), when such a hydrogel is immersed in hydrochloric acid, a neutralization reaction between the hydrochloric acid and the sodium carbonate occurs, and carbon dioxide gas is rapidly generated. When using nonwoven fibers with little intertwining between fibers, such as glass paper, the generation of carbon dioxide gas may cause many air bubbles to be generated in the fiber sheet. Therefore, before immersing in hydrochloric acid (step (b)), the hydrogel may be washed with water to remove the sodium carbonate in the hydrogel.
[0058] The present embodiment will be described below based on examples. However, the present embodiment is not limited to the following examples. All reactions were carried out under air.
[0059] <Evaluation> In the examples, ethylene carbonate was used as a gelling agent, and the silica concentration in the water glass composition was changed to prepare a heat insulating sheet. The bulk density, thermal conductivity, compressibility, and thermal resistance of the obtained heat insulating sheet were evaluated by the following methods.
[0060] The bulk density was calculated from the volume and weight of the heat insulation sheet. The thermal conductivity of the heat insulation sheet was measured using a heat flow meter HFM436Lamda (manufactured by NETZCH). The compressibility of the heat insulation sheet was measured using a tabletop precision universal testing machine Autograph AGS-X (manufactured by SHIMADZU).
[0061] The thermal resistance value of the heat insulating sheet was calculated by dividing the thickness of the heat insulating sheet, which was determined from the compression ratio at a pressure of 5 MPa, by the thermal conductivity.
[0062] The detailed conditions for each of the examples and comparative examples are described below, and the results are shown in Table 1.
[0063] The pass criteria for each evaluation were as follows:
[0064] [Table 1]
[0065] WG: Water glass, ECaq.: Ethylene carbonate aqueous solution, GP: Glass paper (1) Bulk density evaluation The bulk density of the insulation sheet is 0.3g / cm 3 More than 0.6g / cm 3 The following was deemed acceptable: The bulk density of the insulation sheet was 0.3 g / cm 3 If the bulk density is less than 0.6g / cm, the insulation sheet is easily crushed when weight is applied. 3 If the thickness is larger, the sheet will be less likely to collapse under pressure, but the thermal conductivity will be higher and the thermal resistance will be lower. This makes it easier for thermal chain reactions to occur in the insulation sheet when compressed.
[0066] (2) Thermal conductivity evaluation The thermal conductivity of the insulation sheet is rated as passing if it is 100mW / mK or less. If the thermal conductivity of the insulation sheet is higher than 100mW / mK, the thermal resistance will be small, making it easier for a thermal chain reaction to occur when compressed.
[0067] (3) Compression ratio evaluation The compression rate of the heat insulation sheet at 5.0 MPa must be 40% or less to pass the test. Even under high load, in order to effectively suppress thermal chain reaction, the heat insulation sheet must be able to withstand compression to a certain extent and suppress the increase in solid heat transfer components. If the compression rate of the heat insulation sheet at 5.0 MPa is higher than 40%, its superiority over conventional heat insulation sheets is lost.
[0068] (4) Thermal resistance evaluation The thermal resistance of the insulation sheet when compressed at 5.0 MPa is 0.01 m 2 If the thermal resistance was 0.01 m / s or more, it was deemed to have passed. When evaluating thermal resistance, it is sufficient to actually apply a load and measure the thermal conductivity. However, especially when the load is heavy, the sheet collapses under compression, making it difficult to measure the thermal conductivity when compressed. Therefore, the thermal resistance was calculated from the thickness of the insulation sheet calculated from the compression rate and the actual thermal conductivity measured with a heat flow meter HFM, and then compared for evaluation. If the thermal resistance was 0.01 m / s at 5.0 MPa, 2 At less than K / W, thermal chain reaction is more likely to occur during compression.
[0069] (5) Overall rating A product that satisfied all the conditions was deemed to have passed the overall evaluation.
[0070] <Example 1>: (b) Substitution step <1> A water glass composition (100 parts by weight, 20.5 g) (silica concentration 14% by weight) was prepared by diluting a water glass raw material with distilled water, to which 6 parts by weight of an aqueous solution of ethylene carbonate (white crystals) (amount of ethylene carbonate: 1.23 g) was added, and the mixture was thoroughly stirred and dissolved to prepare a basic sol (hereinafter also referred to as "sol solution").
[0071] The sol solution was then applied to nonwoven fabric (material: glass paper, thickness 0.63 mm, basis weight 100 g / m 2The sol solution was poured into a 12 cm square slab to uniformly impregnate the nonwoven fibers. The nonwoven fabric impregnated with the sol solution was sandwiched between two sheets of PP film (50 um thick) and left for 3 minutes at room temperature of 23°C to gel the sol. After gelation was confirmed, the impregnated nonwoven fabric together with the film was passed through a two-axis roll with a gap set to 1.00 mm (including film thickness) to squeeze out excess gel from the nonwoven fabric and regulate the thickness to a target of 1.00 mm.
[0072] Next, the film was peeled off, and the gel sheet was immersed in 6N hydrochloric acid, and then left at room temperature of 23°C for 10 minutes to allow hydrochloric acid to be absorbed into the gel sheet. The gel sheet was then immersed in a mixture of octamethyltrisiloxane, a silylating agent, and 2-propanol (IPA), and placed in a thermostatic chamber at 55°C to react for 2 hours. When trimethylsiloxane bonds began to form, the hydrochloric acid solution was discharged from the gel sheet, and the two liquids were separated (siloxane in the upper layer, hydrochloric acid solution and 2-propanol in the lower layer). The gel sheet was transferred to a thermostatic chamber set at 150°C and dried in air for 2 hours to obtain a heat insulating sheet.
[0073] The thermal conductivity and compression characteristics of this insulation sheet were evaluated, and the compression rate was 35.8% and the thermal resistance value was 0.02m 2 The result was K / W and the overall evaluation was pass.
[0074] <Example 2>: (b) Substitution step <1> A sheet was produced under the same process conditions as in Example 1, except that the silica concentration in the water glass composition was changed to 20% by weight and the amount of ethylene carbonate aqueous solution added was changed to 3 parts by weight. As a result of evaluating this heat insulating sheet, the compression ratio was 21.3% and the thermal resistance value was 0.015 m 2 The result was K / W and the overall evaluation was pass.
[0075] <Example 3>: (b) Substitution step <1> The amount of ethylene carbonate solution added was 6 parts by weight, and the glass paper was 1.08 mm thick and had a basis weight of 170 g / m 2A sheet was produced under the same process conditions as in Example 2, except that the dimensions were changed to 12 cm square. The heat insulating sheet was evaluated, and the compression ratio was 5.4%, the thermal resistance value was 0.022 m 2 The result was K / W and the overall evaluation was pass.
[0076] <Example 4>: (b) Substitution step <2> A sheet was produced under the same process conditions as in Example 3, except that no hydrophobic treatment was performed, i.e., the sheet was dried as is after the film was peeled off. The heat insulating sheet was evaluated, and the compression ratio was 7.2%, the thermal resistance value was 0.012 m 2 The result was K / W and the overall evaluation was pass.
[0077] <Example 5>: (c) Substitution step <3> A sheet was produced under the same process conditions as in Example 3, except that no hydrophobic treatment was performed, that is, after the film was peeled off, the water in the sheet was replaced with 2-propanol (IPA) (23°C, 10 minutes, 200 ml x 2 times) and then dried. The heat insulating sheet was evaluated and found to have a compression ratio of 6.1% and a thermal resistance of 0.016 m 2 The result was K / W and the overall evaluation was pass.
[0078] <Example 6>: (b) Substitution step <4> A sheet was produced under the same process conditions as in Example 3, except that no hydrophobic treatment was performed, that is, after immersion in 6N hydrochloric acid, the hydrochloric acid in the sheet was replaced with distilled water (23°C, 10 minutes, 200 ml x 2 times) and then dried. The heat insulating sheet was evaluated and found to have a compression ratio of 8.6% and a thermal resistance of 0.017 m 2 The result was K / W and the overall evaluation was pass.
[0079] <Example 7>: (b) Substitution step <5> A sheet was produced under the same process conditions as in Example 3, except that no hydrophobic treatment was performed, that is, after immersion in 6N hydrochloric acid, the hydrochloric acid in the sheet was replaced with distilled water (23°C, 10 minutes, 200 ml x 2 times), and the water in the sheet was replaced with 2-propanol (IPA) (23°C, 10 minutes, 200 ml x 1 time), and then the sheet was dried. Evaluation of this heat insulating sheet showed that the compression ratio was 7.9% and the thermal resistance value was 0.017 m 2 The result was K / W and the overall evaluation was pass.
[0080] <Comparative Example 1> A sheet was produced under the same process conditions as in Example 1, except that the silica concentration in the water glass composition was changed to 6% by weight. As a result of evaluating this heat insulating sheet, the compression ratio was 72.5% and the thermal resistance value was 0.013 m 2 The result was K / W, and the overall evaluation was unsatisfactory.
[0081] <Comparative Example 2> A sheet was produced under the same process conditions as in Example 1, except that the silica concentration in the water glass composition was changed to 8% by weight. As a result of evaluating this heat insulating sheet, the compression ratio was 67.3% and the thermal resistance value was 0.015 m 2 The result was K / W, and the overall evaluation was unsatisfactory.
[0082] <Comparative Example 3> A sheet was produced under the same process conditions as in Example 1, except that the silica concentration in the water glass composition was changed to 10% by weight. As a result of evaluating this heat insulating sheet, the compression ratio was 63.8% and the thermal resistance value was 0.015 m 2 The result was K / W, and the overall evaluation was unsatisfactory.
[0083] <Comparative Example 4> A sheet was produced under the same process conditions as in Example 1, except that the silica concentration in the water glass composition was changed to 12% by weight. As a result of evaluating this heat insulating sheet, the compression ratio was 52.4% and the thermal resistance value was 0.016 m 2 The result was K / W, and the overall evaluation was unsatisfactory.
[0084] <Evaluation for each item> (Compressibility of heat insulation sheet) The compression ratio of the heat insulating sheet of the embodiment when pressurized at 5 MPa is preferably 40% or less, more preferably 30% or less. Fig. 3 is a graph showing the relationship between the compression ratio when the heat insulating sheet produced in each Example and Comparative Example is pressurized at 5 MPa and the silica concentration in the water glass composition. If the compression ratio is more than 40%, it is difficult to suppress the thermal chain reaction during compression. If the compression ratio is 40% or less, the thermal chain reaction during compression can be effectively suppressed.
[0085] (Thermal resistance of the insulation sheet) The thermal resistance of the heat insulating sheet of this embodiment when pressurized at 5 MPa is 0.010 m 2 K / W or more is preferable, and 0.015m 2 4 is a graph showing the relationship between the thermal resistance of the heat insulating sheets produced in the examples and comparative examples when pressed at 5 MPa and the silica concentration in the water glass composition. 2 If the thermal resistance is less than 0.015m K / W, it is difficult to suppress the thermal chain reaction during compression. 2 If the compression ratio is 1.0 K / W or more, thermal chain reaction during compression can be effectively suppressed.
[0086] (Thermal conductivity of the insulation sheet) The thermal conductivity of the heat insulating sheet of the present embodiment depends on the compression ratio, and cannot be generally determined, but it is sufficient if it is 100 mW / mK or less. Figure 5 is a graph showing the relationship between the thermal conductivity of the heat insulating sheet produced in each example and comparative example and the silica concentration in the water glass composition. If the thermal conductivity is more than 100 mK / W, it is difficult to suppress the thermal chain reaction during compression.
[0087] (Bulk density of heat insulation sheet) The bulk density of the heat insulating sheet of this embodiment is 0.3 to 0.6 g / cm 36 is a plot of the heat insulating sheets produced in the respective Examples and Comparative Examples, with the silica concentration in the water glass composition at the time of producing the heat insulating sheet plotted on the horizontal axis and the bulk density of the obtained heat insulating sheet plotted on the vertical axis.
[0088] From Figure 6, when ethylene carbonate is used, the bulk density of the heat insulating sheet tends to increase with increasing silica concentration. Bulk density 0.3g / cm 3 If the density is less than 0.6g / cm3, it will be easily crushed when a heavy load is applied. Therefore, the compressibility is large and the thermal resistance is small. Also, if the bulk density is less than 0.6g / cm3, it will be easily crushed when a heavy load is applied. 3 If it is larger, the primary silica particles will become significantly coarser and the aerogel itself will shrink, making it impossible to obtain the expected thermal resistance value even under no load.
[0089] <Summary of results> As described above, in Examples 1 to 7, heat insulating sheets were produced using water glass compositions with silica concentrations of 14 to 20% by weight and ethylene carbonate. As a result, the compressibility at 5.0 MPa was low at 40% or less in all cases, and the thermal resistance value was 0.01 m 2 K / W or more. As shown in Examples 4 to 7, the compressibility and heat resistance were satisfied even without hydrophobization treatment. On the other hand, in Comparative Examples 1 to 4, heat insulating sheets were produced using water glass compositions with silica concentrations of 6 to 12% by weight and ethylene carbonate. As a result, the compressibility at 5.0 MPa was all greater than 40%.
[0090] From the above results, it was found that the heat insulating sheet made of high-density aerogel-nonwoven fiber synthesized using a water glass composition with a silica concentration of 14 to 20% by weight and carbonate ester is excellent as a high-strength heat insulating sheet and is effective in suppressing thermal chain reaction even under high load conditions.
[0091] <Other> The heat insulating sheet contains aerogel and nonwoven fabric fibers as main components, and does not contain other compounds as main components, and the total weight of the aerogel and nonwoven fabric fibers is 90% or more by weight of the total weight of the heat insulating sheet.
[0092] Generally, silica aerogel refers to a low-density porous silica body, with a bulk density of approximately 0.3 g / cm. 3 In order to obtain such a low-density porous silica body, a hydrophobic (water-repellent) treatment is usually carried out after step (a) in order to prevent irreversible shrinkage during drying. However, in the manufacturing method of the present invention, the silica concentration is set to 14 to 22% by weight, which is higher than usual, to provide a strength capable of withstanding the capillary force during drying, so that the desired heat insulating sheet can be obtained without carrying out a hydrophobic (water-repellent) treatment.
[0093] FIG. 7 shows an application example 1 of the heat insulating sheet of the embodiment. FIG. 7 is a diagram showing a schematic configuration of an electronic device having a heat generating electronic component 12 and a housing 11. The heat insulating sheet 10 of the embodiment can be disposed between the heat generating electronic component 12 and the housing 11 in the electronic device. The heat insulating sheet 10 of the embodiment does not transfer heat from the electronic component 12 to the housing 11. The electronic component 12 is mounted on a substrate 13. The heat insulating sheet 10 may be covered with a cover that covers the surface. The heat insulating sheet 10 may be laminated with a thermally conductive material, for example, a graphite sheet.
[0094] FIG. 8 shows a second application example of the heat insulating sheet of the embodiment. FIG. 8 is a diagram of a battery unit having a plurality of batteries for use in an automobile or the like. In such a battery unit, if the heat insulating sheet 10 of any of the above-mentioned embodiments is placed between the batteries 15, not only can the heat be insulated between the batteries 15 but also the spread of fire can be prevented, which is preferable. The battery 15 is not limited to that for automobiles. The battery 15 may be a battery for various mobile objects or a battery for a home power storage device. The heat insulating sheet 10 may be combined with other sheets, etc. [Industrial Applicability]
[0095] The heat insulating sheet of this embodiment, which is made of at least two components, high density aerogel and nonwoven fiber, and has improved compressive strength, can be widely used because it can provide sufficient heat insulating effect even in narrow spaces inside electronic devices, in-vehicle devices, and industrial devices. It can be applied to all products related to heat, such as information devices, mobile devices, displays, and electrical equipment. [Explanation of symbols]
[0096] 10. Insulation sheet 11. Cabinet 12 Electronic Components 13 Substrate 15 Batteries 101 Sodium silicate 102 Hydroxyl ion 103 Ethylene carbonate 104 Carbonate ion 105 Ethylene glycol 106 Hydrogels 107 Sodium Carbonate
Claims
1. Aerogel and and fibers including at least one of inorganic fiber-based fibers, resin-based fibers, and natural fibers; The compressibility at 5.0 MPa is 40% or less, A heat insulating sheet having a thermal resistance of 0.01 m 2 K / W or more when compressed at 5.0 MPa.
2. The heat insulating sheet according to claim 1, having a thickness of 0.03 mm or more and 3.0 mm or less.
3. The aerogel has a specific surface area of 300 m 2 / g or more 600m 2 3. The heat insulating sheet according to claim 1 or 2, having a pore volume of less than 1.5 ml / g.
4. Bulk density is 0.3 g / cm 3 0.6g / cm or more 3 The heat insulating sheet according to any one of claims 1 to 3, wherein:
5. The heat insulating sheet according to any one of claims 1 to 4, wherein the weight percentage of the aerogel in the heat insulating sheet is 50% by weight or more.
6. The heat insulating sheet according to any one of claims 1 to 5, wherein the inorganic fiber-based fibers include at least one selected from glass wool, glass paper, and rock wool.
7. The heat insulating sheet according to any one of claims 1 to 5, wherein the resin-based fibers include at least one selected from the group consisting of polyethylene terephthalate, polyphenylene sulfide, polypropylene, and polytetrafluoroethylene.
8. The heat insulating sheet according to any one of claims 1 to 7, wherein the fibers constitute a nonwoven fabric.
9. Electronic components that generate heat; A housing that houses the electronic components; The heat insulating sheet according to any one of claims 1 to 8, The electronic device, wherein the heat insulating sheet is disposed between the electronic component and the housing.
10. A number of batteries; The heat insulating sheet according to any one of claims 1 to 9 is provided, The battery unit, wherein the insulating sheet is disposed between the plurality of batteries.
Citation Information
Patent Citations
Method of operating sump pump facility
JP1984034400A
Instrument equipped with filter
JP1985064149A
Vacuum heat insulating material
JP2004197760A
Fiber-reinforced cement lightweight panels
JP2008526665A
Molded body, enclosure, method of producing the molded body and method of producing cutting element
JP2012240251A
